A Retrospective Cohort Study Evaluates Clinical Value of Anlotinib in Persistent, Metastatic, or Recurrent Cervical Cancer After Failure of First-Line Therapy - Yang H; Sun S; Mei Z; Xiang Q; Yang C; Chen M; Xie C; Zhou Y; Qiu H (Dove Medical Press, 2021)
Hui Yang,1- 3 Shaoxing Sun,1- 3 Zijie Mei,1- 3 Qingming Xiang,1- 3 Chunxu Yang,1- 3 Min Chen,1- 3 Conghua Xie,1- 3 Yunfeng Zhou,1- 3 Hui Qiu1- 3 1Department of Radiation and Medical Oncology, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of China; 2Hubei Key Laboratory of Tumor Biological Behaviors, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of China; 3Hubei Cancer Clinical Study Center, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of ChinaCorrespondence: Hui Yang; Hui QiuDepartment of Radiation and Medical Oncology, Hubei Key Laboratory of Tumor Biological Behaviors, Hubei Cancer Clinical Study Center, Zhongnan Hospital of Wuhan University, 169 Donghu Road, Wuhan, 430071, People's Republic of ChinaEmail huiyangwhu@whu.edu.cn; qiuhuiznyy@whu.edu.cnBackground: Anlotinib is an oral anti-angiogenesis inhibitor targeting vascular endothelial growth factor receptors (VEGFRs), platelet-derived growth factor receptors, fibroblast growth factor receptors, etc., and its clinical value in cervical cancer is rarely reported. We designed a retrospective study to evaluate the efficacy and safety of anlotinib in patients with persistent, metastatic, or recurrent cervical cancer who have failed first-line therapy, and compare the efficacy of anlotinib with that of apatinib which targets only VEGFR2 and has shown efficacy in recent studies.Methods: Fifty-two patients with persistent, metastatic, or recurrent cervical cancer who failed first-line therapy and administrated anlotinib or apatinib as monotherapy or combination with chemo-, radio- or immunotherapy were included in this study. Among the 52 patients, 20 patients who received anlotinib from January 2019 to August 2020 were defined as anlotinib group, whereas 32 patients who received apatinib from our previous study were selected as apatinib group. The safety, objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS) were reviewed and recorded.Results: The ORR and DCR in patients receiving anlotinib were 25% and 80%, respectively. The median PFS and OS in anlotinib group were significantly longer than those in apatinib group, respectively (PFS: 5 months vs 3 months, p=0.015; OS: 10 months vs 5 months, p=0.008). Moreover, the patients treated with anlotinib had better survival with a significantly lower cumulative incidence of cancer-related death than those treated with apatinib (HR=0.31, 95% CI: 0.13- 0.77, p=0.012). The most common adverse effects in the patients treated with anlotinib were hypertension (20%), fatigue (20%), and nausea (15%). No drug-related death occurred.Conclusion: Anlotinib showed beneficial efficacy and safety and can be a treatment option for patients with persistent, metastatic, or recurrent cervical cancer who have failed the first-line therapy.Keywords: angiogenesis, anlotinib, cervical cancer, efficacy, safety, retrospective study